2014
DOI: 10.1590/s1413-70542014000600002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of three rootstocks on yield and commercial quality of "Italian Sweet" pepper

Abstract: Pepper crops (Capsicum annuum L.) represent a very important production sector in the Southeast of Spain. Specifically, in the province of Almería, approximately 7000 hectares are grown every year. Due to the economic importance that this crop has for the region and the withdrawal of soil fumigants from the market, agronomic techniques have been adopted with the aim of controlling some soil pathogens and increasing the yield and quality parameters of the fruits obtained. The use of grafted pepper plants is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 18 publications
(22 reference statements)
1
8
0
Order By: Relevance
“…For instance, Doñas-Uclés et al (2014) demonstrated an increase in fruit weight when cv. Palermo was grafted onto the C. annuum rootstock ‘Tesor,’ whereas the use of rootstocks ‘Oscos’ and ‘AR40’ incurred a minimal increase in fruit weight.…”
Section: The Configuration Of Fruit Quality In Grafted Vegetablesmentioning
confidence: 99%
“…For instance, Doñas-Uclés et al (2014) demonstrated an increase in fruit weight when cv. Palermo was grafted onto the C. annuum rootstock ‘Tesor,’ whereas the use of rootstocks ‘Oscos’ and ‘AR40’ incurred a minimal increase in fruit weight.…”
Section: The Configuration Of Fruit Quality In Grafted Vegetablesmentioning
confidence: 99%
“…However, among these vegetables, grafting is a less common practice in peppers, probably because commercial rootstocks provide modest profits [ 12 , 13 ]. Several scientific reports have reported the effects of rootstock on pepper fruit quality, such as morphometric and yield characteristics [ 14 , 15 ], sweetness/acidity [ 16 , 17 ], or levels of functional compounds [ 18 , 19 ]. Another peculiarity of pepper is its aroma [ 20 ], which has become a quality parameter for consumers [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The lowest yield in non-grafted plants was due to the decrease in fruit mean mass and number of fruits per plant (COLLA et al, 2006). In the grafted plants more yield was reported in some vegetables such as pepper (GISBERT et al, 2010;DONAS-UCLES et al, 2014), melon (RICÁRDEZ-SALINAS et al, 2010), tomato (IBRAHIM et al, 2001) and watermelon (MIGUEL et al, 2004; YETISIR and SARI, 2019). Concerning fruit dry matter, significantly highest fruit dry matter was produced by 'ERÜ 1227' grafted onto 'Scarface' rootstock followed by non-grafted control plants of 'ERÜ 1227', while the lowest was shown by the 'ERÜ 1227' grafted onto '46 KB F1' rootstock and '33 H-3-1' grafted onto 'Scarface' rootstock (Table 1).…”
Section: Number Of Fruits Per Plant Fruit Yield Fruit Dry Matter Smentioning
confidence: 98%
“…However, the use of grafting in pepper plants is not as common as in the rest of horticultural species mainly due to the lack of commercial rootstocks that perform satisfactorily (LEE et al, 2010), in spite of the fact that the use of appropriate rootstocks can be an alternative strategy to avoid or reduce yield losses caused by environmental stresses (SINGH et al, 2017). So far, slight attention has been paid to the effect of grafting and rootstocks on grafted pepper vegetative growth, fruiting characteristics and yield has been investigated in few studies and with only a limited number of rootstocks (TSABALLA et al, 2013;DONAS-UCLES et al, 2014;SOLTAN et al, 2017). For all these reasons, the use of pepper grafted plants is not yet widely implemented in Turkey.…”
Section: Introductionmentioning
confidence: 99%